Note about the "Iberian" inscription from Elda (G.11.1) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The main concern of this note is to correct a wrong attribu-tion for the inscription G.11.1 from the necropolis El Monastil at Elda (Alicante) that until now has been assumed to be a paleohispanistic inscription, even though it has a later chronology.
Keywords: Palaeohispanic epigraphy; Byzantine Epigraphy; Palaeohispanic corpus; Elda (Alicante)